Rilievo Aerofotogrammetrico e Cartografia in Campo Archeologico: Casi Applicativi nel sito di UÅŸakli Höyük (Turchia) - Regine, Vincenzo (Archeomatica, 2020)
This paper examines the use of digital photogrammetry and terrain data management within GIS applied to Archaeology, i.e. the study and reconstruction of the settlement layout of UÅŸaklÄ± Höyük (Central Anatolia, Turkey) during the Hittite period, through 3D surveys and geo-spatial analyses. Thanks to the data acquisition and processing using algorithms software, i.e. Structure for Motion and Multi-view stereo, it was possible to create highresolution photogrammetric products and cartographic maps valuable for interpreting and further examining archaeological evidence collected during excavations. These products include: i) Digital Elevation Models (DEM), ii) 3D textured models, iii) aerial photogrammetric survey of the Hittite temple (Building II) at a scale of 1:200 and, iv) the orthophoto map of the höyük at a scale of 1:500.